Development of novel photocatalytic materials for wastewater treatment - Berkesi Dániel; Sharma Nikita; Szabó Szilvia; Hernádi Klára; 30th International Symposium on Analytical and Environmental Problems Szeged 2024. október 7-8. (University of Szeged Szeged, 2024)
The growing concern over environmental pollution, particularly from pharmaceutical wastewater, has driven the need for advanced treatment methods[1]. Photocatalysis, an ecofriendly and efficient approach, holds significant promise for the degradation of persistent organic pollutants[2]. This study focuses on the development and characterization of novel photocatalytic materials, including basic bismuth nitrate (BBN)[3], ilmenite (FeTiO3)[4], and bismuth-decorated titanium dioxide (TiO2) nanoparticles. The primary goal is to synthesize these semiconductor materials using grind-assisted and hydrothermal methods, optimize their structural properties, and test their photocatalytic efficiency in degrading pharmaceutical pollutants[5]. The research also includes the design of a photocatalytic reactor with multiple light sources and temperature control to ensure reliable performance testing under various conditions[2], [6]. The outcomes of this work will contribute to bridging gaps in the literature, offering insights into the synthesis of effective photocatalysts and their application in wastewater treatment.
Keywords: Természettudományok; Kémiai tudományok